Um estudo fonético-acústico sobre róticos em variantes do espanhol - Cóstola, Maria da Piedade Soares (2017)
Rhotics are a sound class, which presents extensive allophonic variation in coda position. Knowledge on the use of rhotic variants is of interest to the teaching of Spanish to Brazilian students, as grapheme-phoneme correspondence in Spanish differs from that in Portuguese. Two rhotic phonemes are present in the Spanish language, tap / ɾ / and trill /r/, and taps, trills, fricatives, fricative vibrants and approximants can occur as allophones in coda position. Rhotics in coda position can also be omitted. In this work, based on the Acoustic Theory of Speech Production, supported by the auditory evaluation of rhotics categories and the inspection of wide band spectograms, which allows us to inferer the position of the articulators, we were able to detail the phonic features of rhotic sounds. The corpus consisted of the lyrics to the song "Pedro Navaja", written by Rubén Blades, read by seven female native Spanish speakers, who were tasked with reading the text three different times. The seven speakers represented six varieties of Spanish: Colombian (S1), Cuban (S2), Peruvian (S3, S7), Spanish (S4), Argentine (S5), and Mexican (S6). The analysis of rhotics production in coda position showed a greater number of tap realizations in all contexts examined and by all speakers. The production of the expressive words revólver, mujer, sorpresas was not homogeneous among the subjects. The data obtained from the sociolinguistic survey matches the findings from the speech production analysis. Beyond adding to the growing knowledge on the use of rhotics in Spanish, this work can also contribute to the teaching of Spanish language to Brazilians, and inspire the creation of teaching and learning materials that deal with pronunciation in a qualified manner